MIGRASI TRADISI PESANTREN JAWA KE MALAYSIA AWAL ABAD KE-20 - Mohd Taufik Arridzo; Bani Sudardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
This article reveals the Java pesantren tradition in Malaysia, especially ini the main areas where Javanese peole live, such as negeri Selangor, Perak and Johor. The discussion focuses on three kiai who come from Java and got education in Java pesantren and build pesantren in Semenanjung Tanah Melayu. They are a part of outstanding kiai who built pesantren in those three negeri. They represent the three negeri: Kyai Muhammad Ali Qaribun (from Bantul, Yogyakarta) in Selangor, Kyai Salleh(from Purworejo,Jawa Tengah) in Perak dan Dato‘ Kyai Shamsuddin Ridhwan (from Madiun Jawa Timur) in Johor. The result of the research shows that in the end of 19 century until the beginning of 20 there were many Javanese migrated to Semenanjung Melayu. They came from various places in Java and migrated there for some reasons; spreading religion, hate the colonialism, and the need of survive. The kiai continued the Java pesantren tradition in Semenanjung Melayu. They still have good relationship with their ancestral land in Java so they still send their santri to Java to continue the study.